Alleviation of Postharvest Chilling Injury of Carambola Fruit by γ-aminobutyric Acid: Physiological, Biochemical, and Structural Characterization - Ngaffo Mekontso, Francine; Duan, Wenhui; Cisse, El Hadji Malick; Chen, Tianye; Xu, Xiangbin (Frontiers in Nutrition, 2021)
1 Chilling injury (CI) is a physiological disorder affecting the quality of carambola fruit through different biological processes. In last decades, several studies were focused on the effect of exogenous γ-aminobutyric acid (GABA) to understand the strategies by which GABA counteract with chilling injury in plant. However, the interactions between GABA, membrane stability and the saturated and unsaturated fatty acid are still lacking. Thus, the present study aimed to investigate the effect of GABA on CI development in carambola fruit. The results showed that exogenous GABA reduced CI index, weight loss, respiration rate, maintained pericarp lightness, flesh firmness, and decreased the electrolyte leakage and malondialdehyde content while increased the enzyme activities (SOD, POD, CAT and LOX). Moreover, the proline and acid ascorbic content was promoted by GABA under stress. During the stress period, GABA-treated fruit exhibited a higher activity of phenylalanine ammonia-lyase and total of phenolic compounds, and a lower activity of polyphenol oxidase. Moreover, the Safranin O/fast green staining revealed via microscopic images that the GABA treatment reduced the cell walls degradation of carambola fruit. After 15 d of treatment, the results displayed an enhancement of the content of oleic acid (C18:1), linoleic acid (C18:2n6), and α-linolenic acid (C18:3n3), which could maintain membrane’s integrity and prevent the rapid softening of carambola fruit. The findings of the present work showed particularly new insights into the crosstalk between GABA and the fatty acids. GABA might preserve the pericarp of carambola fruit by increasing the content of the unsaturated fatty acid γ-linolenic acid and reducing progressively the saturated fatty acid such as caproic acid (C6:0), caprylic acid (C8:0), myristic acid (C14:0) and palmitic acid (C16:0).